Dynamics of Internalization and Intracellular Interaction of Tau Antibodies and Human Pathological Tau Protein in a Human Neuron-Like Model - Shamir, Dov B.; Deng, Yan; Wu, Qian; Modak, Swananda; Congdon, Erin E.; Sigurdsson, Einar M. (Frontiers in Neurology, 2020)
We and others have shown in various in vivo, ex vivo and cell culture models that several tau antibodies interact with pathological tau within neurons. To further clarify this interaction in a dynamic human model, we differentiated SH-SY5Y cells with retinoic acid and BDNF to create a neuron-like model. Therein, tau antibodies were primarily taken up by receptor-mediated endocytosis, and prevented toxicity of human brain-derived paired helical filament-enriched tau (PHF). Subsequently, we monitored in real-time the interaction of antibodies and PHF within endocytic cellular compartments. Cells were pre-treated with fluorescently-tagged PHF and then incubated with tau antibodies, 4E6, 6B2, or non-specific isotype control IgG1 labeled with a pH sensitive dye. The uptake and binding of the efficacious antibody, 4E6, to PHF occurred mainly within the soma, whereas the ineffective antibody, 6B2, and ineffective control IgG1, were visualized via the processes and showed limited colocalization with PHF within this period. In summary, we have developed a neuron-like model that clarifies the early intracellular dynamics of the interaction of tau antibodies with pathological tau, and identifies features associated with efficacy. Since the model is entirely human, it is suitable to verify the therapeutic potential of humanized antibodies prior to extensive clinical trials.